2019
DOI: 10.5093/psed2019a4
|View full text |Cite
|
Sign up to set email alerts
|

Escala de Funcionamiento Ejecutivo para Escolares: Análisis de las Propiedades Psicométricas

Abstract: A B S T R A C TThis paper presents the psychometric properties and an initial validation study of the Executive Functioning Scale for Children (EFS). The EFS assesses parents' and teachers' perception of the frequency of certain behaviors schoolchildren may present when performing tasks that demand attentional control, inhibitory control, metacognition, organization, planning, and cognitive flexibility. The participants were 307 schoolchildren, male and female (48.2% female), between 6 and 10 years of age (M =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 35 publications
1
2
0
1
Order By: Relevance
“…To this end, the scale proposed in this article will allow new research to be carried out that will benefit university students and their performance which in turn will favor their professional training and, therefore, have a positive impact on society (Ramos-Galarza and Pérez-Salas, 2016). The results of this research are consistent with previous studies that have found adequate psychometric properties to assess executive functions in various settings, for example, the study carried out by Korzeniowski and Ison (2019) who developed a scale in a school setting with executive functions: attention regulation, metacognition, inhibitory regulation, organization, planning, and flexibility. In another study, that of García et al (2018), a scale was analyzed to assess executive functions in a family setting and took into consideration inhibition, hyperactivity, emotion regulation, concentration, focus, organization, working memory, and flexibility as executive functions.…”
Section: Discussionsupporting
confidence: 90%
“…To this end, the scale proposed in this article will allow new research to be carried out that will benefit university students and their performance which in turn will favor their professional training and, therefore, have a positive impact on society (Ramos-Galarza and Pérez-Salas, 2016). The results of this research are consistent with previous studies that have found adequate psychometric properties to assess executive functions in various settings, for example, the study carried out by Korzeniowski and Ison (2019) who developed a scale in a school setting with executive functions: attention regulation, metacognition, inhibitory regulation, organization, planning, and flexibility. In another study, that of García et al (2018), a scale was analyzed to assess executive functions in a family setting and took into consideration inhibition, hyperactivity, emotion regulation, concentration, focus, organization, working memory, and flexibility as executive functions.…”
Section: Discussionsupporting
confidence: 90%
“…Sin embargo, el acceso al instrumento es pago y los baremos de la escala fueron realizados sobre población española. Por último, el tercer instrumento es la Escala de Funcionamiento Ejecutivo (Korzeniowski & Ison, 2019), desarrollada en Argentina y que evalúa la percepción de progenitores y docentes acerca del comportamiento presentado por niños de entre 6 y 10 años al realizar tareas que demanden control ejecutivo. Posee 30 ítems divididos en seis subescalas: control atencional, control inhibitorio, metacognición, organización, planificación y flexibilidad cognitiva.…”
Section: ¿Cómo Se Evalúan Tradicionalmente Las Fe?unclassified
“…On the other hand, studies agree on a gradual increase in care capacities in the age group of 5 to 16 years (Matute et al, 2009)Likewise, in urban-marginal schools, as age increases, there is an increase in cognitive ability (Ison and Anta, 2006), another study states that from the age of 7, attentional performance increases until the age of 17 (Carrada, 2013)In sum, our results are linked to neurological maturation in which the period of greatest development between 6 and 8 years and a moderate increase between 9 and 12 years is indicated (Tirapu-Ustárroz et al, 2018) In other analyzes, the results reveal that, the Eo decrease according to the school grade, this is attributable to the maturity that the subjects obtain as they acquire greater cognitive abilities. In addition, the ICI increases in blocks from 1° to 3° and 4° to 6°, that is, the subjects as they scale to higher grades have better impulsive control in attentional tasks, consequently, it indicates an adequate inhibitory control in different learning contexts (Korzeniowski & Ison, 2019)Oh, yeah. Finally, variability in Ec results is evident, in contrast, studies indicate that as subjects mature Ec decreases (Miranda, et al, 2008, Miranda, et al Al.…”
Section: Analysis Of Results According To School Gradementioning
confidence: 97%